Long-Term Survival in Gastroesophageal Junction Adenocarcinoma: Ramucirumab - Gil-Delgado, Maria Angeles (Case Rep Gastroenterol, 2018)
We report a case of long-term survival with complete response of liver metastases within RAINBOW, a randomized, controlled trial of ramucirumab 8 mg/kg intravenously (days 1, 15) versus placebo, both plus paclitaxel 80 mg/m(2) intravenously (days 1, 8, 15), every 4 weeks in patients with previously treated advanced gastroesophageal junction adenocarcinoma. A 64-year-old man with gastroesophageal junction adenocarcinoma and liver metastases received first-line folinic acid, 5-fluorouracil plus oxaliplatin (FOLFOX) following jejunostomy. On liver progression, he enrolled in RAINBOW (April 2012), receiving ramucirumab. In November 2013, positron emission tomography scan was consistent with complete metabolic response, confirmed by a follow-up scan in March 2016.